The Effectiveness of BOD Performance and ERM on Company's Financial Performance - Butar-butar, Dea Tiara Monalisa; Indrianto, Doni (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
The purpose of this research is to examine the correlation between corporate financial performance as assessed by Return on Asset (ROA) and the efficacy of the Board of Directors (BOD), more especially board size, board independence, and board gender. Enterprise Risk Management (ERM) is a moderating variable, and the chief risk officer's function is a surrogate for it in this study. Financial reports of 45 companies registered on the Indoensia Stock Exchange for the years 2018–2022, making up the bulk of the data used in this analysis. According to the findings, ROA is significantly affected by board independence but unaffected by board size or gender. Also, this study finds that ERM has moderating effect on the relationship between board independence and ROA.